Regulation of cardiac output and venous return - Saunders, W. B. (1975)
Since the heart is the organ which actually pumps blood through the circulation, it at first may seem logical to assume that the activity of the heart is the primary factor determining cardiac output. However, such is not the case, and a few key observations serve to illustrate this point: In experimental animals and humans, it has been demonstrated that greatly increasing cardiac pumping by increasing heart rate with no change in the peripheral circulation does not appreciably increase cardiac output. Replacing the heart in experimental animals with a powerful artificial pump does not increase the "cardiac" output. Reducing peripheral vascular resistance by opening a large A-V shunt increases the rate of return of blood to the heart and cardiac output without changing the heart rate or the contractility of the heart. In animals with denervated hearts and adrenal demedullation (to prevent an increase in circulating catecholamines), cardiac output still increases when venous return increases during moderate exercise. However, at extremely high levels of exercise, the capacity of the heart to pump becomes a limiting factor. These observations demonstrate that as long as the pumping capacity of the heart is greater than venous return, the actual cardiac output is determined by the venous return. It may be viewed that under normal conditions, the heart plays a permissive role, pumping whatever blood returns to it as long as it is able to do so. Two conditions in which the cardiac pumping ability is less than the tendency for venous return are severe cardiac failure and extremely strenuous exercise. Under these conditions, the activity of the heart itself becomes the limiting factor to and the determinant of cardiac output. Since both the pumping capability of the heart, its permissive role, and the tendency for venous return determine the cardiac output, it is necessary to examine the factors influencing each of these.